2017
DOI: 10.1177/2167702617724424
|View full text |Cite
|
Sign up to set email alerts
|

What Drives False Memories in Psychopathology? A Case for Associative Activation

Abstract: In clinical and court settings, it is imperative to know whether posttraumatic stress disorder (PTSD) and depression may make people susceptible to false memories. We conducted a review of the literature on false memory effects in participants with PTSD, a history of trauma, or depression. When emotional associative material was presented to these groups, their levels of false memory were raised relative to those in relevant comparison groups. This difference did not consistently emerge when neutral or nonasso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 154 publications
0
44
2
Order By: Relevance
“…The GSS 2 narrative was reasonably neutral and makes no reference to sexual abuse; although the narrative involves a child having an accident on his bicycle and calling for help (i.e., a minor stressful event). It is unlikely that "associative" or "spreading" activation explains our findings (Otgaar et al, 2017).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The GSS 2 narrative was reasonably neutral and makes no reference to sexual abuse; although the narrative involves a child having an accident on his bicycle and calling for help (i.e., a minor stressful event). It is unlikely that "associative" or "spreading" activation explains our findings (Otgaar et al, 2017).…”
Section: Discussionmentioning
confidence: 68%
“…This data is supported by the results of the study by Gudjonsson et al (2016), where the additional procedure for measuring delayed suggestibility was standardised on a sample of 1,182 minors. Otgaar et al (2017) argue that there is "no theoretically convincing explanation" as to why neutral false memories and not-associative material should be activated in individuals with PTSD (p. 1057). In the current study the misleading information incorporated into memory was peripheral rather than central, which increases the likelihood of its acceptance (Eisen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…To conclude, research has suggested that EMDR and thus eye movements are effective as a treatment for PTSD, but the current work is the first showing that eye movements can have adverse effects. This finding combined with recent work showing that individuals with PTSD are at increased risk to create false memories ( Otgaar, Muris, Howe, & Merckelbach, 2017 ) and work showing that therapists have poor knowledge on issues concerning memory ( Patihis et al, 2014 ) stresses the importance of conducting follow-up research on the drawbacks of EMDR.…”
Section: Discussionmentioning
confidence: 86%
“…Spreading activation theories (e.g., Howe et al, 2009) suggest that related concepts, such as the DRM list items, are embedded within an associative network and that the presence of an item (e.g., the word piano ) activates a corresponding concept (see also Otgaar, Muris, Howe, & Merckelbach, 2017). Most importantly, according to these theories, activation will automatically spread to “nearby” related concepts (e.g., music ) and the level of activation determines the rate of recall/recognition (Anderson, 1983).…”
mentioning
confidence: 99%